Potential therapeutic effects of Cordyceps cicadae and Paecilomyces cicadae on adenine-induced chronic renal failure in rats and their phytochemical analysis - Li L; Zhang T; Li C; Xie L; Li N; Hou T; Wang Y; Wang B (Dove Medical Press, 2018)
Ling Li,1,* Tong Zhang,1,* Chunru Li,2 Lu Xie,3 Ning Li,4 Tianling Hou,1 Yuqin Wang,2 Bing Wang1 1Experiment Center for Teaching and Learning, Shanghai University of Traditional Chinese Medicine, Shanghai, China; 2Zhejiang BioAsia Pharmaceutical Co., Ltd., Pinghu, Zhejiang, China; 3Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, China; 4Institute of Chinese Materia Medica, Shanghai University of Traditional Chinese Medicine, Shanghai, China *These authors contributed equally to this work Background: Natural Cordyceps cicadae (C. cicadae) has been utilized extensively in traditional Chinese medicine to treat chronic renal diseases, heart palpitations, infantile convulsions, and dizziness. However, given its slow growth and immoderate exploitation, C. cicadae resources have been severely depleted. By contrast, Paecilomyces cicadae (P. cicadae), as the anamorph stage of C. cicadae, is easy to cultivate, and this kind of cultivated P. cicadae has good and controllable quality. Purpose: This study aimed to compare the therapeutic effects of C. cicadae and P. cicadae on adenine-induced chronic renal failure (CRF) rats. In accordance with the aforementioned studies, our work subsequently analyzed the intrinsic relationships between the efficacy and pharmacodynamic substances of C. cicadae and P. cicadae to conclude whether or not P. cicadae could be used as an alternative to C. cicadae in treating CRF. Methods: Rats were administered with C. cicadae (1.0 g/kg) or P. cicadae (1.0 g/kg) by gavage for 4 weeks. Furthermore, we applied Fourier transform infrared spectroscopy, gas chromatography–mass spectrometry, liquid chromatography–tandem mass spectrometry, and ultraviolet spectrophotometry to comprehensively detect and analyze the chemical constituent differences from ten batches each of C. cicadae and P. cicadae. Results: This study revealed that both C. cicadae and P. cicadae exerted obvious therapeutic effects on CRF and were more consistent with their chemical compositions. Conclusion: P. cicadae can be used as an alternative to C. cicadae for treating CRF to cater to market demands. Keywords: Cordyceps cicadae, Paecilomyces cicadae, chronic renal failure, FTIR, GC-MS, LC-MS/MS, identification